Investigating the Equation and the Area of Ellipse Using Circular Cylinder Section Approach - H A Rohman; A Jupri (Pascasarjana Universitas Pendidikan Indonesia, 2019)
An ellipse can be obtained through the conic section, if the plane intersects one of the pieces of the cone and its axis but is not perpendicular to the axis, the intersection will be an ellipse. Besides that, a cylinder cut by a plane that has a slope between 00 and 900 against the base of the cylinder, the intersection forms an ellipse. The purpose of this study that 1) determine the equation of the ellipse in terms of the circular cylinder section approach and 2) determine the area of the ellipse in terms of the circular cylinder section approach The method we used in this research is literature studies from several books that are relevant to research. The results showed that 1) the equation of ellipse can be derived from the approach of circular cylinder section and 2) the area of the ellipse can be obtained using the circular cylinder section approach. We conclude using this circular cylinder section approach, we can obtain the same formula both for equation and area as the conic section.